8‐Hydroxy Quinoline Derivatives as Auxiliary Ligands for Red‐Emitting Cyclic‐Platinum Phosphorescent Complexes: Synthesis and Properties. Issue 4 (4th March 2017) - Li, Zhimei; Yu, Liming; Yuan, Junshuo; Ye, Yiteng; He, Yanbo; Huang, Bin; Gao, Xicun
Abstract : Heavy metal complexes exhibit high phosphorescent efficiency and have been used extensively for electrophosphorescent emitters in the past 16 years. In 2006, we initially reported the use of the popular ligand, 8‐hydroxyquinoline (Q) to coordinate with the heavy metal ions and obtained the red‐infrared phosphorescent emission. In this paper, 8‐hydroxyquinoline has been modified at the 5‐position by electron‐donating and attracting groups and platinum complexes based on 2‐phenylpyridine and 8‐hydroxyquinoline derivatives were synthesized. The electron‐withdrawing group CF3 and NO2 lowers the HOMO level of the Q ligand and results in a N^O centered enhanced red‐infrared phosphorescence emission. The complex with CF3 modification exhibits the highest phosphorescence quantum yield in solid state with a life time of 1.17 μs. Abstract :